2009
DOI: 10.1016/j.brainres.2008.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor tractography quantification of the human corpus callosum fiber pathways across the lifespan

Abstract: Several anatomical attributes of the human corpus callosum (CC) including the midsagittal cross-sectional area, thickness, and volume, have been used to assess CC integrity. We extended our previous lifespan quantitative diffusion tensor imaging (DTI) study of the regional CC midsagittal areas to include the CC volumes obtained from DTI fiber tracking. In addition to the entire CC tracked subvolumes we normalized volume with respect to each subject’s intracranial volume (ICV) and the corresponding DTI metrics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
130
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(158 citation statements)
references
References 50 publications
28
130
0
Order By: Relevance
“…This drop in fractional anisotropy in the isthmus relative to the other segments of the corpus callosum has not been observed in healthy individuals (Hasan et al, 2008).…”
Section: Resultsmentioning
confidence: 58%
“…This drop in fractional anisotropy in the isthmus relative to the other segments of the corpus callosum has not been observed in healthy individuals (Hasan et al, 2008).…”
Section: Resultsmentioning
confidence: 58%
“…The qualitative evaluation of white matter bundles crossing frontal transcortical approaches revealed that the access through either superior or medial frontal gyrus at least partially sectioned following tracts: division I and II of SLF, 2 sub-volumes of rostral corpus callosum (CC1/CC2 [22]), pyramidal and corticoreticular tracts. The presented result was consistently noted in every analysed hemisphere (22 of 22; 100%).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have investigated the anatomical and functional characteristic of the CC in humans 2,7,9,10,13,16,18,25) . These studies investigated the thickness, volume, and area information of the CC to provide accurate anatomical information 9,10,25) .…”
Section: Discussionmentioning
confidence: 99%
“…DTI provides a noninvasive method for visualizing white matter structures in the brain. Diffusion tensor tractography (DTT), based on DTI data, enables 3D neural fiber tract visualization, and has been used to identify major white matter pathways, such as the corticobulbar, corticospinal, and associated fiber tracts 8,16,18,19) . Moreover, combining DTT with functional magnetic resonance imaging (fMRI) provides more accurate information for in vivo analysis of the brain 7,[20][21][22] .…”
Section: Introductionmentioning
confidence: 99%